Persistent activation of Nrf2 promotes a vicious cycle of oxidative stress and autophagy inhibition in cadmium-induced kidney injury. (December 2021) - Fan, Rui-Feng; Tang, Kou-Kou; Wang, Zhen-Yong; Wang, Lin
Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) serves as the master regulator of antioxidant signaling and inhibition or hyperactivation of Nrf2 pathway will result in the redox imbalance to induce tissue injury. Herein, we established cadmium (Cd)-exposed rat kidney injury model by intraperitoneal injection with CdCl2 (1.5 mg/kg body weight) and cytotoxicity model of NRK-52E cells by CdCl2 (5 μM) exposure to reveal the role of Nrf2 hyperactivation in Cd-induced nephrotoxicity. Data from the in vitro and in vivo study showed that Cd caused Nrf2 nuclear retention due to nuclear-cytoplasmic depletion of Kelch-like ECH-associated protein 1 (Keap1) and Sequestosome-1(SQSTM1/p62) accumulation, leading to the persistent activation of Nrf2. Moreover, we established inhibited models of Cd-induced prolonged Nrf2 activation using siRNA-mediated gene silencing in vitro and pharmacological inhibition in vivo for subsequent assays. First, Cd-induced cytotoxicity, renal injury and concomitant oxidative stress were markedly alleviated by Nrf2 inhibition. Second, Cd-induced autophagy inhibition was notably alleviated by Nrf2 inhibition. Further, we revealed underlying molecular mechanisms of the crosstalk between persistent activation of Nrf2 and autophagy inhibition in Cd-induced nephrotoxicity. Data showed that Cd-induced lysosomal dysfunction evidenced by impaired lysosomal biogenesis and degradation capacity was markedly recovered by Nrf2 inhibition. Meanwhile, Cd-impaired autophagosome-lysosome fusion was obviously restored by Nrf2 inhibition. In conclusion, our findings revealed that persistent activation of Nrf2 promoted a vicious cycle of oxidative stress and autophagy inhibition in Cd-induced nephrotoxicity.